Penerapan Algoritma AES 128-Bit dalam Pengamanan Data Kependudukan pada Dinas Dukcapil Kota Pematangsiantar - Imelda Asih Rohani Simbolon; Indra Gunawan; Ika Okta Kirana; Rafiqa Dewi; S Solikhun (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Population data is information about the existence of someone in a country. The data can be accepted as validity through management in one of the government agencies. The issue of security and confidentiality of the data is something that is very important because it concerns the identity of a person, in order to avoid theft and manipulation of data it is necessary to apply a data security system. Cryptography is the study of mathematical techniques related to aspects of data and information security such as data validity, integrity, and data authentication. The Advanced Encryption Standard (AES) is one method used in data / information safeguards. The implementation of the AES algorithm in securing population data of the Population and Civil Registration Service shows that the method can produce messages that cannot be read or understood by humans (encryption) and produce the same message as the initial plaintext that was imputed (decryption)